Detection of local Bacillus subtilis producing Endo-β-1,4-glucanase Of Thi Qar province - Ali Kassab, Mohammed; Laibi Chelab, Rahman (University of Thi-Qar Journal of Science, 2018)
The study included  isolating  and  diagnosing of Bacillus subtilis  different soils at  Thi Qar province. The ability of bacterial isolates to produce Endo-β-1,4-glucanase was determined after growing on carboxymethyl cellulose CMC medium, Using Congo red and NaCl.  Enzyme  Endo-β-1,4-glucanase  isolates were  identified using   biochemical tests and VITEK2 as B. subtilis. Isolates were identified using  16S rRNA tests after extraction of DNA from isolates and amplified by PCR using 27F primers (Forward) and 1492R  (Reverse) . All isolates in the current study were positive for this gene and the size of the gene for all isolates was at 1500 pb. After identifying the gene sequences and comparing them with the data available in the Gen Bank, NCBI  data  showed  that they were  new  strains of B. subtilis strain m1 (MF449304) and B. subtilis strain M2 (MF449461) bacteria. Isolates were recorded in NCBI GenBank and were design for each evolutionary tree isolation by Software MEGA6. After the diagnosis of bacterial  isolates, the ideal conditions for the production of Endo-β-1,4-glucanase were changed for incubation period, temperature, pH , Incubator Shake, carbon and   nitrogen sources. Enzymatic efficacy was determined using of dinitro salicylic acid DNS detector to detect the glucose releasing  glucose molecules  Endo-β-1,4-glucanase. The enzyme was  produced  after growing of bacterial  isolates of  plant  culture containing  plant and cardboard residues as natural sources of carbon and alternative to costly industrial sources as a source of carbon  at a concentration of 1%  at  45 ° C for 48 hours .